2022
DOI: 10.1021/acs.jpclett.2c01694
|View full text |Cite
|
Sign up to set email alerts
|

A Plausible Mechanism of Uracil Photohydration Involves an Unusual Intermediate

Abstract: It is well-known that photolysis of pyrimidine nucleobases, such as uracil, in an aqueous environment results in the formation of hydrate as one of the main products. Although several hypotheses regarding photohydration have been proposed in the past, e.g., the zwitterionic and “hot” ground-state mechanisms, its detailed mechanism remains elusive. Here, theoretical nonadiabatic simulations of the uracil photodynamics reveal the formation of a highly energetic but kinetically stable intermediate that features a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…A similar lifetime has also been obtained using MRSF-TDDFT. 48 Although it is not readily discernible in Figure 7b, the 1 ππ* lifetime for Ura is even shorter than that for Thy. The signal intensity integrated over 4−5.4 eV decays in 15 ± 1 fs (Figure 7d), and the global fitting analysis provides time constants of 17 ± 1 fs, 0.44 ± 0.01 ps, 3.48 ± 0.03 ps, and >30 ps (Figure S19).…”
Section: ■ Experimental Sectionmentioning
confidence: 83%
“…A similar lifetime has also been obtained using MRSF-TDDFT. 48 Although it is not readily discernible in Figure 7b, the 1 ππ* lifetime for Ura is even shorter than that for Thy. The signal intensity integrated over 4−5.4 eV decays in 15 ± 1 fs (Figure 7d), and the global fitting analysis provides time constants of 17 ± 1 fs, 0.44 ± 0.01 ps, 3.48 ± 0.03 ps, and >30 ps (Figure S19).…”
Section: ■ Experimental Sectionmentioning
confidence: 83%
“…In particular, because the photon absorption results in a π → π* transition in the S 1 state, this leads to recoupling of the single and double bonds in the molecule, which manifests itself in the bond length alternation (BLA) displacement. This is because the bright ππ * transition is mainly composed of a HOMO (π) to LUMO (π*) single electron excitation yielding a π 1 π 1 * configuration, which effectively eliminates a single π bonding from its π-conjugation network. Therefore, in the vicinity of the Franck–Condon (FC) geometry on the excited state potential energy surface (PES) there exists a substantial slope in the BLA direction, which results in a rapid motion along this mode. However, the period of oscillatory BLA motion is rather short (∼20 fs) and the experimental observation of coherent BLA motion should require pump pulses of extremely short duration, i.e., a very broad bandwidth, a condition that is not usually fulfilled in the experiments.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages allow the MRSF to overcome the major limitations of the conventional TDDFT variants, while reliably reproducing the results of the more expensive multi-reference ab initio wave function theories. 9 In a series of studies, 8,12,[14][15][16][17][18][19][20][21][22] it has been demonstrated that the MRSF approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs), 15,17 enabling reliable non-adiabatic molecular dynamics (NAMD) simulations, [22][23][24] a topologically correct description of conical intersections, 8,18,21 and accurate values of singlet-triplet gaps. 14,16 This method has also been successfully used in designing high-performance optoelectronic materials.…”
Section: Introductionmentioning
confidence: 99%